Kompleks düzlemde kapalı ve bağlantılı kümelerde bazı sürekli fonksiyon sınıflarının yapısal karakterizasyonu - Doğu, Öznur (My University, 2020)
In this thesis; on quasi-conform arcs in terms of estimates depending on the point constructive characteristic of classes of the functions has been obtained. On more general continua in terms of uniform estimates (in terms of estimates independent of the point) constructive characterization of classes of functions has been investigated. To obtain these results in addition to estimating the devition of functions from polynomials, additional information has been given on the growth of the derivative of polynomials. In addition, in this thesis, depending on the end points of the arc in the complex plane, the class of functions has been defined. In this class of the functions the approximation of the functions by polynomials has been investigated. After, on arcs with certain properties of the complex plane constructive characterization of classes of functions has been obtained.
Constructive characterization of some classes of some classes of continuous functions in closed and connected sets in the complex plane
Keywords: Kuasikonform yay; En iyi yaklaşım; Süreklilik modülü; Yaklaşım karakterizasyonu